Model Sistem Pengelolaan Hutan Alam Setelah Penebangan dengan Sistem Tebang Pilih Tanam Indonesia (TPRI) - Indrawan, Andry (Jurnal Manajemen Hutan Tropika, 2003)
The study discribes a system model of natural forest on logged over areas under selective cutting and planting system. The study departs from a fact that disturbance of forest from logging activity will affect the equilibrium of forest ecosystem including the forest stand composition. The study was performed in the forest concession area of PT. Inhutani II, Pulau Laut South Kalimantan. From the simulation results derived based upon permanent plot data, it was found that respond of logged over natural forest management system revealed that cutting cycle I after logging requires approximately 24 years, where cutting cycle II requires approximately 37 years. This expresses that cutting cycles are not consist and will change in line with the composition and structure of logged over natural forest as will as their development.